Strengthening the Role of Prospective Teachers as Agents of Resilience and Innovation through Disaster Preparedness Education and Digital Entrepreneurship Mentoring for PPG Students at IPI Garut - Yaman Suryaman; Galih Abdul Fatah Maulani; Nizar Alam Hamdani (Indonesian Journal of Community Empowerment (IJCE), 2026)
Garut Regency faces a high risk of natural disasters amidst a rapidly evolving digital era that demands continuous innovation; consequently, this community service initiative was designed to strengthen the capacity of Teacher Professional Education (PPG) students at the Institute of Education Indonesia (IPI) Garut to act as dual agents resilient in the face of disasters and skilled in digital innovation. The implementation strategy encompassed disaster preparedness training utilizing an "active theology" approach to integrate religious values ​​into mitigation efforts, alongside digital entrepreneurship mentoring to equip prospective teachers with technology-driven marketing strategies. Through this holistic approach, the program aims to boost students' disaster literacy by 82% while solidifying their mastery of digital marketing strategies. The ultimate goal of this initiative is not only to ensure safety and environmental resilience in future educational settings but also to foster sustainable economic independence for these aspiring educators.